Los derechos de propiedad, la acción colectiva y las tecnologías para el manejo de los recursos naturales - Knox, Anna; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 1999)
Degradation of natural resources has be come a global probelem that threatens the livelihood of millions of poor people. Many promising technologies for natural resource management are available to address these problems, but farmers and others often fail to adopt them. Why is this? Although many factors can be identified, lack of secure property rights and collective action deserve greater attention from policy makers and technology developers.